AN ANALYSIS OF DIRECTIVE SPEECH ACT IN ELON MUSK’S SPEECH ON WORLD WATER FORUM - Fajar, Rizkyta Naufal; Aisyah, Siti; Hesturini, Esther (IKIP Siliwangi, 2024)
Speech acts need to be understood in a speech because they contain various communication acts that create emotional and cognitive impacts on the audience. This study aims to identify the types of directive speech acts in Elon Musk's speech at the 10th World Water Forum and determine the most dominant type of directive speech acts. The method used in this research is qualitative. The data were obtained from the video transcript of Elon Musk's speech. The data collection process was conducted through text and video analysis, and analyzed with three stages: data reduction, data display, and conclusion drawing. The results show that in Elon Musk's speech, there are various types of directive speech acts such as giving orders, asking, inviting, forbidding, and suggesting. The frequency of the use of these directive speech acts varies, with 2 data of speech commanding, 2 speech requesting, 1 speech inviting, 1 speech forbidding, and 1 speech suggesting. So it was found that the types of directive speech acts such as commanding and requesting dominated in Elon Musk's speech at the World Water Forum.